2007
DOI: 10.1105/tpc.106.048272
|View full text |Cite
|
Sign up to set email alerts
|

Unique, Shared, and Redundant Roles for theArabidopsisSWI/SNF Chromatin Remodeling ATPases BRAHMA and SPLAYED

Abstract: Chromatin remodeling is emerging as a central mechanism for patterning and differentiation in multicellular eukaryotes. SWI/SNF chromatin remodeling ATPases are conserved in the animal and plant kingdom and regulate transcriptional programs in response to endogenous and exogenous cues. In contrast with their metazoan orthologs, null mutants in two Arabidopsis thaliana SWI/SNF ATPases, BRAHMA (BRM) and SPLAYED (SYD), are viable, facilitating investigation of their role in the organism. Previous analyses reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(174 citation statements)
references
References 78 publications
6
154
0
6
Order By: Relevance
“…The BRM transcript level was 1.5-fold higher than that of ATSWI3C in all organs. These results were also consistent with a previous RT-PCR study of ATSWI3C transcript levels by Bezhani et al (2007).…”
Section: Comparison Of Transcription Prowles Of Atswi3c and Brmsupporting
confidence: 93%
“…The BRM transcript level was 1.5-fold higher than that of ATSWI3C in all organs. These results were also consistent with a previous RT-PCR study of ATSWI3C transcript levels by Bezhani et al (2007).…”
Section: Comparison Of Transcription Prowles Of Atswi3c and Brmsupporting
confidence: 93%
“…Furthermore, BRM was shown to repress ABSCISIC ACID INSENSITIVE5, a key positive regulator of ABA signaling, by binding to its promoter and regulating ABA-dependent nucleosome rearrangement . Although BRM and SYD are thought to perform partially overlapping functions, SYD interacts preferentially with the SWI3A and B core subunits, a binding partner of FCA required for FLC expression, whereas the binding partners of BRM in the SWI/SNF core are SWI3B and SWI3C (Sarnowski et al, 2002;Bezhani et al, 2007). For the majority of target genes showing altered transcription in SWI/ SNF subunit mutants, the composition of SWI/SNF complexes and their interacting transcription factor partners are thus far unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that similarly to the BRM, SYD, and SWI3 subunits of SWI/SNF complexes (Sarnowski et al, 2005;Bezhani et al, 2007;Archacki et al, 2009), their associated SWP73 factors are likely involved in the control of vegetative-to-generative phase transition and/or regulation of floral homeotic genes. In fact, analogously to BRM, which was found to control the transcription of flowering time repressor FLC (Farrona et al, 2011), Jégu et al (2014 reported recently that SWP73B modulates chromatin loop formation at the FLC locus.…”
Section: Swp73a and Swp73b Play Distinct Roles In Flowering Time Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, several components of these complexes are evolutionarily conserved in plants, such as the SWI3 subunits (Sarnowski et al, 2005), the SNF5/BSH subunit (Brzeski et al, 1999), the nuclear actin-related protein ARP4 , BRAHMA (BRM), or SPLAYED (SYD). Both of these latter proteins are ATPases of Arabidopsis SWI/SNF complexes and have been shown to participate in the control of flower development and flowering time (Wagner and Meyerowitz, 2002;Farrona et al, 2004;Hurtado et al, 2006;Bezhani et al, 2007;Fornara et al, 2010;Wu, 2012). Likewise, the SWI3B protein interacts with the flowering regulator FCA (Sarnowski et al, 2005).…”
Section: Introductionmentioning
confidence: 99%